12th IET International Conference on Developments in Power System Protection (DPSP 2014) 2014
DOI: 10.1049/cp.2014.0041
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated voltage control scheme for Flemish LV distribution grids utilizing OLTC transformers and D-STATCOM's

Abstract: The incorporation of on-load tap changers (OLTC) in secondary distribution transformers has been proposed as alternative technology to prevent the violation of the voltage statutory limits in Flemish LV distribution grids. Under high penetration levels of distributed generation (DG), this device can partly eliminate those violations increasing the voltage unbalances when independent tap-changing control per phase is applied. The paper describes a coordinative scheme for the regulation of positive and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The OLTC is activated when the D‐STATCOM is insufficient. The D‐STATCOM can mitigate the VU and current harmonics [75]. The PVs inverters can coordinate with OLTC instead of D‐STATCOM.…”
Section: Voltage‐violation Mitigation Strategiesmentioning
confidence: 99%
“…The OLTC is activated when the D‐STATCOM is insufficient. The D‐STATCOM can mitigate the VU and current harmonics [75]. The PVs inverters can coordinate with OLTC instead of D‐STATCOM.…”
Section: Voltage‐violation Mitigation Strategiesmentioning
confidence: 99%
“…Similarly, in [31], a method of joint control was proposed, through the operation of OLTC and reactive power control in the inverter. In [17], an attempt to combine OLTC work with the operation of distributed static compensators (D-STATCOM) was described. The aim of the work was to achieve better dynamics and continuity of control.…”
Section: Centralized and Decentralized Control Strategiesmentioning
confidence: 99%
“…If i is the index of the node with the maximum measured voltage, reduction in voltage required (∆u) to ensure no over voltage occurs is calculated using Equation (20).…”
Section: Active Power Reduction Calculationmentioning
confidence: 99%
“…Results showed that not only does use of D-STATCOM improves voltage regulation, it also suppresses harmonic distortion [19]. A coordinated control strategy for OLTC and D-STATCOM has been presented in [20]. The authors have concluded that proposed scheme is capable of mitigating both over voltages and voltage imbalances via active and reactive power control respectively.…”
Section: Introductionmentioning
confidence: 97%